ANALISIS KINERJA KEUANGAN PADA KANTOR CAMAT BATANGHARI LEKO KABUPATEN MUSI BANYUASIN MENGGUNAKAN PENDEKATAN VALUE FOR MONEY - Septariani, Jumania; Romanda, Candra (Institut Rahmaniyah Sekayu, 2025)
This study seeks to evaluate the degree to which financial performance management is grounded on the Value For Money strategy utilized at the Batanghari Leko District Office, Musi Banyuasin Regency. The data included in this research comprised Budget Outcomes from 2021 to 2023. This study employed a quantitative methodology and was done in the Batanghari Leko District Office in Musi Banyuasin Regency. The data sources comprised both primary and secondary sources, utilizing interviews and documentation for data collection procedures. The Batanghari Leko District Office in Musi Banyuasin Regency has effectively managed its resources, leading to the conclusion that its financial performance management is exceptional.